Acquisition and establishment of the oral microbiota. Issue 1 (10th March 2021) - Kaan, A. M. (Marije); Kahharova, Dono; Zaura, Egija
Abstract: Acquisition and establishment of the oral microbiota occur in a dynamic process over various stages and involve close and continuous interactions with the host and its environment. In the present review, we discuss the stages of this process in chronological order. We start with the prenatal period and address the following questions: 'Is the fetus exposed to maternal microbiota during pregnancy?' and 'If so, what is the potential role of this exposure?' We comment on recent reports of finding bacterial DNA in placenta during pregnancies, and provide current views on the potential functions of prenatal microbial encounters. Next, we discuss the physiological adaptations that take place in the newborn during the birth process and the effect of this phase of life on the acquisition of the oral microbiota. Is it really just exposure to maternal vaginal microbes that results in the difference between vaginally and Cesarian section‐born infants? Then, we review the postnatal phase, in which we focus on transmission of microbes, the intraoral niche specificity, the effects of the host behavior and environment, as well as the role of genetic background of the host on shaping the oral microbial ecosystem. We discuss the changes in oral microbiota during the transition from deciduous to permanent dentition and during puberty. We also address the finite knowledge on colonization of the oral cavity by microbes other than the bacterial component. Finally, we identify the main outstanding questions that limit our understanding of the acquisition and establishment of a healthy microbiome at an individual level.